Molecular Evolutionary Analyses of Euplotes Species Living in Freshwater and Marine Habitats: A Mitogenomic Perspective - Huang, Ning; Chen, Shuai; He, Ming; Song, Qi; Hou, Lina; Zhao, Yan; Zhao, Shuo; Miao, Miao (Frontiers in Marine Science, 2021)
Ciliates are the most complex unicellular eukaryotic organisms, which play important roles in various ecosystems. The Euplotes is a dominant genus in the ciliates Euplotida and consists of approximate one hundred species. They distribute widely in environments with various salinity levels including freshwater, brackish, seawater as well as hypersaline. In this study, we obtained four mitochondrial genomes of Euplotes species, using both high throughput sequencing and Sanger sequencing. Combined with two previously reported Euplotes mitochondrial genomes, we analyzed their gene structure, codon usage pattern as well as phylogenetic relationship. We found that gene rearrangement exists in Euplotes and codon usage bias is different among these species. Phylogenetic analyses based on both mitochondrial and nuclear genes further unveiled that Euplotes spp. living in similar salinity levels tend to be clustered together. Moreover, we found that the dN/dS ratios of two mitochondrial genes, cox1 and cox2, are significantly different between marine and freshwater species, indicating the salinity could act as a barrier for the Euplotes species distribution. We also recommended mitochondrial genes to discriminate the species with highly similarity of Euplotes which could not be easily distinguished by nuclear gene marker and morphological characteristics. This study provides novel resources to improve our understanding of Euplotes evolution and also its adaptation to habitats with different salinity levels.